Preoperative transversus abdominis plane block decreases intraoperative opiate use during pancreatoduodenectomy. Issue 7 (July 2022) - Zárate Rodriguez, Jorge G.; Leigh, Natasha; Edgley, Carla; Cos, Heidy; Wolfe, Rachel; Sanford, Dominic; Hammill, Chet W.
Abstract: Background: Multimodal analgesia and regional anesthetic blocks, such as transversus abdominis plane (TAP) block, decrease postoperative opiate consumption but their effect on intraoperative opiates is unknown. Methods: This was a retrospective review of patients undergoing pancreatoduodenectomy between June 2018 and February 2021, in which perioperative data, operative times, and medication administration data were collected. Intraoperative opiate use was calculated in total morphine equivalent doses (MED) for each patient and adjusted for operative time. Univariate analysis and multivariate linear regression were performed to determine factors affecting intraoperative opiate requirements. Results: Of the 169 patients in the study, 51 (30.2%) received pre-surgical TAP blocks and 118 (69.8%) did not. There were no statistically significant differences in intraoperative opiate use with preoperative acetaminophen (p = 0.527), celecoxib (p = 0.553), gabapentin (p = 0.308), intraoperative ketorolac (p = 0.698) or epidural placement (p = 0.086). Minimally invasive surgery had lower intraoperative opiate use compared to open (p = 0.011), as well as pre-surgical TAP block compared to no pre-surgical block (5.24 vs 7.27 MED/hour, p < 0.001). On multivariate linear regression, pre-surgical TAP block (p = 0.001) was independently associated with decreased intraoperative opiate use. Conclusion: Preoperative TAP blocks were associated with decreased intraoperative opiate use during pancreatoduodenectomy and should be considered for routine use.